Potential for Development of Bumdes Wates Village, Jenangan District in the Culinary Sector to Improve Village Economy - Tricahyono, Widakdo; Hidayati, Anindya; Galuh , Adhek; Laela, Emi; Widiyahseno, Bambang (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
The existence of BUMDes (Village-Owned Enterprises) is a national initiative designed to enhance the economic welfare and public services of villages across Indonesia. According to Law No. 6 of 2014, establishing BUMDes is mandatory for all villages, including Wates Village in the Jenangan District. This study focuses on the potential of BUMDes in Wates Village, particularly within the culinary sector, to act as economic drivers. The primary objective is to evaluate how BUMDes can foster the development of Micro, Small, and Medium Enterprises (MSMEs) in the community by enhancing product branding and marketing reach. Using a qualitative research method, data were collected through interviews, field observations, and literature reviews from relevant sources such as books, journals, and websites. Triangulation was employed to ensure the validity of the collected data. The findings indicate that BUMDes can significantly contribute to economic growth in Wates Village by providing essential support to local culinary MSMEs. This support includes improving branding strategies, expanding marketing reach, and offering training programs. The study concludes that with targeted interventions, BUMDes can effectively elevate the economic status of village communities, aligning with Indonesia's national principle of improving community welfare at all levels.